Animated Video-Based Problem-Based Learning Model Containing Local Balinese Wisdom on Students' Problem-Solving and Cooperation Abilities in Science Subjects of Grade VI Elementary School - Ni Putu Ellys Sucitha Dewi; I Wayan Lasmawan; Ida Bagus Putrayasa (Indonesian Journal of Instruction, 2026)
Education plays an important role in developing students’ higher-order thinking and social skills. However, problem-solving and collaboration skills in science learning remain low due to conventional learning models that lack active student engagement and local wisdom integration. This study aims to analyze the effect of implementing a Problem Based Learning (PBL) model supported by animated videos incorporating local wisdom on students’ problem-solving and collaboration skills. This study employed a quasi-experimental method with a nonequivalent control group design, involving sixth-grade students as research subjects, consisting of an experimental group and a control group. Data were collected through tests to measure problem-solving skills and questionnaires to assess collaboration skills, using instruments that had been validated and tested for reliability. Data analysis was conducted using descriptive statistics, prerequisite tests (normality, homogeneity, and multivariate normality), and hypothesis testing through MANOVA and ANOVA. The results indicate that the implementation of the PBL model supported by animated videos incorporating local wisdom has a significant effect on students’ problem-solving and collaboration skills, both simultaneously and partially. Therefore, this model is effective in improving the quality of science learning. The implications of this study suggest that integrating PBL with animated video media based on local wisdom can serve as an innovative instructional strategy to enhance student engagement, critical thinking, and collaboration skills.